Analysis of Youth Engagement in Rice Production in North Central, Nigeria - D.A, Agbonika; Idisi P.O (International Journal of Applied and Scientific Research, 2024)
This study evaluated youth engagement in rice production in selected states of north central, Nigeria. In this study, primary data was used and the data was collected through the use of structured questionnaire. Data collected were analysed using descriptive statistics, stochastic production frontier. The results showed that 79% of the producers were male. This indicates the dominance of male in rice production. Among the producers, youths who are ≤ 20 years (24%) engaged in weeding, 20% of youths who are 21-30 years engaged in land clearing activities. Determining the technical efficiency in rice production seed (p<0.01), fertilizer (p<0.01), labour (p<0.01) were among the significant factors. Result of the inefficiency model of technical efficiency revealed that sex, age, marital status, educational status had positive coefficient. Variability in prices of rice was ranked as the foremost constraints militating against the performance of rice producers as asserted by 95% of the respondents. From the finding it is therefore, recommended that rice producer should be encouraged and sensitized in their production activities in order to attain self-sufficiency in rice production.